Microfinance, A Lifeline for Micro Industries in Pakistan: A Comparison of Governmental and Non-Governmental Microfinance Programs - Muhammad Umar Farooq; Rukhshanda Anjum (Journal of Management Practices, Humanities and Social Sciences, 2023)
The association of microfinance and entrepreneurship is increasingly recognized as a tool for the socio-economic development of dawdling regions. By contrast, most of the studies on the micro level have primarily focused on poverty alleviation and spending of loans on living standards and reached conflicting findings. Evidence on the impact of microfinance on entrepreneurial development in different regions has conflicting results. There is growing academic interest in geographical variations and a consensus that geographical disparities exist. This paper investigates the impact of microfinance programs offered by government and non-government organizations on the profitability, employment and sales growth of microenterprises operating in Pakistan. Using a sample of borrowers (treatment group) and respondents on the waiting list (control group) operating microenterprises, we provide evidence that the impact on the profitability of microenterprises is positive, with a higher mark for NGO borrowers. Moreover, the study's novelty compares the microenterprise industry and the findings that using loans in service sector business makes individuals more likely to move from a low-wage labourer to a more profitable entrepreneurship status. Our findings will help policymakers and academics identify the most relevant intervention areas.